When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

Articulation famille-travail : exploration auprès de mères pratiquant le travail du sexe - Deslauriers, Annick (Université du Québec à Montréal, 2023)
Malgré l’entrée massive des femmes sur le marché du travail et les avancées que l’on doit aux mouvements féministes, le patriarcat demeure un paradigme dominant à l’égard de la question familiale (Descarries et Corbeil, 2002ª). Dans sa version plus contemporaine, le consensus social concernant la famille est aussi imprégné de l’influence de l’épidémiologie sociale, un paradigme qui supporte une ambition scientiste et normative (Parazelli et al., 2003 et Parazelli, 2013). Comme la mère porte implicitement la responsabilité de l’ordre familial et par extension, de l’ordre social, cette normativité est étroitement liée au genre (Cardi, 2007; 2010 et 2015). Cette recherche s’ancre dans les épistémologies féministes. Elle propose une démarche qualitative, exploratoire et critique en s’intéressant à la réalité des mères qui pratiquent le travail du sexe à partir de l’idée selon laquelle « on ne peut être mère et putain à la fois » (Ovidie, 2018). Le stéréotype de la mère s’oppose effectivement à celui de la putain dans l’imaginaire social (Descarries et Mathieu, 2009). Les mères qui pratiquent le travail du sexe doivent ainsi réconcilier leur posture d’être humain discrédité en regard de leur travail et leur identité de mère, laquelle est soumise à des injonctions normatives de plus en plus élevées (Samtani et Trejos-Castillo, 2015). Nous exposons les données issues d’entrevues semi-dirigées réalisées auprès de huit mères exerçant le travail du sexe afin d’explorer leur expérience de l’articulation famille-travail. Cette expérience est traversée par la gestion des temps et des espaces de la vie familiale et du travail, laquelle relève surtout de la mobilisation de stratégies personnelles par les mères. Ces constats correspondent aux connaissances portant sur l’articulation famille-travail (Descarries et Corbeil 2002ᵇ; Malenfant, 2002; Tremblay, 2003 et Seery, 2014 et 2020). S’agissant des mères que nous avons rencontrées, cette expérience a cependant de particulier qu’elles doivent composer avec le stigmate de putain (Pheterson, 2001). Nous avons donc recours à certains travaux portant sur la stigmatisation symbolique et structurelle aux fins d’analyse et de discussion de nos résultats de recherche. On relève deux grands types de stratégies employées par ces femmes pour faire face au stigmate de putain : elles s’en distancient ou elles lui résistent. La valorisation dans le travail compte parmi les stratégies de résistance. À ce sujet, elles énoncent des réalités et des compétences se rapportant au travail du care. Ainsi, la perspective du care est également mobilisée dans notre cadre conceptuel. Nous réfléchissons notamment au travail du sexe comme travail du care à la lumière des concepts de travail émotionnel (Hochschild, 2003 et 2012), de sale boulot (Lhuilier, 2005 et Molinier 2011) et de défenses collectives féminines et viriles (Molinier, 2000; 2002 et 2004), alors qu’une part importante du travail du care demeure stigmatisée en tant que sale boulot (Molinier, 2011) et que le travail émotionnel est sous-pesé dans l’appréhension de la valeur du travail du care (Molinier, 2011 et 2020). De plus, bien que la dimension du care soit transversale aux activités de soins et de services aux personnes, elle est généralement occultée du sexuel (Molinier, 2009 et 2011). Ces idées nous permettent d’éclairer le discrédit porté à l’endroit des mères pratiquant le travail du sexe et de réfléchir à leurs avenues de reconnaissance et de citoyenneté. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : travail du sexe, mères, articulation famille-travail, féminisme, patriarcat, imaginaire social, discours sociaux dominants, significations imaginaires sociales, stigmatisation, stigmate de putain, travail du care, travail émotionnel, sale boulot, défenses collectives
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; canada; care; conciliation famille-travail; discipline; famille; patriarcat; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail; travail du sexe; travail social

La charge mentale et l'anxiété qui en découle - Spill the Tea (2023)
Aujourd’hui, on jase avec vous de la charge mentale et de tout se qui en découle. Ne nous faisons pas de cachette, le rôle de maman apporte une énorme charge mentale pour la plupart d’entre nous et nous avions envie de s’ouvrir sur le sujet. On espère que l’épisode saura vous apaiser et vous montrer que vous n’êtes pas seules.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; anxiété; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé mentale des mères; thématiques; travail

The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

"I am willing to do both well": Chinese academic mothers facing tension in family and career. - Bao, Li; Wang, Guanghua (Frontiers in psychology, 2022)
Academic mothers perform intersected roles. They carry out their profession in workplaces, while they take the "second shift" of motherhood back to their families. The contested expectations in family and career built by the heterosexual matrix cause tension to academic mothers. We qualitatively investigate the interview data of six Chinese women academics on how they perform to negotiate their motherhood and academic work in the context of Chinese higher education, driven by the Butlerian theoretical concept of the heterosexual matrix. The findings suggest that Chinese academic mothers play a zero-sum game between being mothers and being academics, deriving from their ontological responsibilities of motherhood. We conclude that in the masculine academia, these women academics help maintain the heterosexual matrix by satisfying the gender normativity when they negotiate their performances in their family and career; meanwhile, most have developed some strategies to achieve their career advancement.; Competing Interests: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest. (Copyright © 2022 Bao and Wang.)
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; chine; conciliation famille-travail; famille; femmes* universitaires; hétérosexisme; maternité; matrice hétérosexuelle; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail

Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie

COVID-19 and gender inequity in science: Consistent harm over time - Caldarulo, Mattia; Olsen, Jared; Frandell, Ashlee; Islam, Shaika; Johnson, Timothy P; Feeney, Mary K; Michalegko, Lesley; Welch, Eric W (PLoS One, 2022)
Stay-at-home-orders, online learning, and work from home policies are some of the responses governments, universities, and other institutions adopted to slow the spread of COVID-19. However, research shows these measures have increased pre-existing gender disparities in the workplace. The working conditions for women during the pandemic worsened due to increased family care responsibilities and unequal distribution of domestic labor. In the academy, working from home has resulted in reduced research time and increased teaching and family care responsibilities, with a larger proportion of that burden falling to women. We investigate the persistence of gender inequity among academic scientists resulting from university COVID-19 responses over time. We draw on two surveys administered in May 2020 and May 2021 to university-based biologists, biochemists, and civil and environmental engineers, to analyze how the pandemic response has disproportionately impacted women in academia and the endurance of those inequities. Results show significantly greater negative impacts from the pandemic on women’s research activities and work-life balance, compared to men. We conclude by discussing the implications of our results, and the need for the academy to better predict and adjust to the gender disparities its policies create.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; covid-19; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; thématiques; travail; travail gratuit; états-unis

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit

D'invisibles à héroïnes. Élever la voix des femmes pour un monde meilleur - Le Capitaine, Catherine (Éditions JFD, 2022)
"Les dénonciations des femmes victimes de violence et d'harcèlement, qui font prendre conscience de l'ampleur des inégalités persistances entre les sexes, suscitent à l'heure actuelle un regain d'intérêt du féminisme. Malgré l'édition de nombreux ouvrages spécialisés sur divers thèmes liés aux femmes ici au Québec et ailleurs dans le monde, aucun, à notre connaissance, n'a adopté une appréciation plus globale de la situation historique et contemporaine des femmes au Québec. L'ouvrage que nous proposons vise à sensibiliser les étudiant.e.s et, plus largement, tout type de public, sur les progrès considérables réalisés au fil du temps (l'accès à l'éducation, le droit de vote, les droits des femmes au travail, etc.) et, surtout, sur l'ampleur du travail restant à accomplir en termes de droits, de violence, de travail, de hors travail, de pouvoir d'agir, etc. pour atteindre l'égalité des sexes. Il portera principalement sur l'histoire et les enjeux contemporains des femmes au Québec et au Canada, tout en souhaitant présenter, par un encadré par exemple, quelques données ou faits marquants provenant d'un autre pays dans le monde."– Fourni par l'éditeur
Keywords: amériques; conciliation famille-travail; corps; environnement; famille; projet charge mentale; québec; ressource en ligne; régions géographiques; santé; spiritualité; thématiques; travail

Pas ce soir, chéri, j’ai mal à la tête (parce que je fais ton lavage) - Massicolli, Elisabeth (Gazette des femmes, 2022)
Quel est le lien entre la charge mentale et l’épanouissement sexuel des femmes au sein des couples hétérosexuels? On fait le point. Dans le livre Women Who Run With the Wolves, la psychanalyste Clarissa Pinkola Estés écrit : « Il y a cette drôle de chose à propos du nettoyage de la maison… c’est que c’est une tâche qui n’est jamais terminée. C’est la façon parfaite d’empêcher une femme de faire quoi que ce soit d’autre. » L’autrice parle ici du processus créatif : elle affirme que l’art ne peut pas être pratiqué que dans des moments « volés », entre une brassée de lavage et la préparation du souper. Que l’art prend du temps et que l’artiste doit agir avec ses pulsions et, pour y arriver, être en mesure de se reposer.
Keywords: 2000 à aujourd'hui; approches et analyses; charge mentale; conciliation famille-travail; famille; hétérosexisme; projet charge mentale; périodes historiques; ressource en ligne; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

Les effets de la crise sociosanitaire de la COVID-19 sur la charge mentale des femmes : le vécu de travailleuses de la région de Chaudière-Appalaches. Synthèse - Seery, Annabelle; Forest, Danielle; St-Germain, Lise (Trois-Rivières: Centre de recherche sociale appliquée (CRSA), 2022)
Fiche synthèse 1. Objectifs Intentions : Le but de cette recherche est de «documenter l’impact de la crise sociosanitaire sur la charge mentale des travailleuses de la région [de la Chaudière-Appalaches].» (p. 3) 2. Méthode Échantillon/Matériau : L’échantillon est constitué de 22 femmes résidentes de Lévis, âgées entre 26 et 45 ans. La majorité de ces femmes «occupe un emploi à temps plein et a travaillé au moins une partie de la 1re année de pandémie en télétravail.» (p. 4) De plus, la majorité des participantes habitent avec leur partenaire et ont des enfants.» (p. 4) Instruments : Guide d’entretien semi-directif Type de traitement des données : Analyse de contenu 3. Résumé Les résultats montrent que «[l]a fermeture des écoles et des services de garde de même que la diminution du soutien disponible ont entrainé une augmentation de la charge de travail des femmes au sein de leur famille.» (p. 6) Les résultats révèlent également que «[l]es femmes sont demeurées les responsables du travail à réaliser dans la famille, en plus de voir s’ajouter la responsabilité de l’école à la maison ou le casse-tête de la garde des enfants. [De plus], [l]es femmes proches aidantes ont aussi vu leur charge de travail augmentée en répondant aux besoins de leurs proches dépendants.» (p. 6) Aussi, «[l]es femmes qui ont fait du télétravail ont rencontré plusieurs difficultés à cause du contexte particulier dans lequel elles ont dû travailler (notamment avec les enfants à la maison).» (p. 6) Enfin, les résultats mettent en lumière que «[l]es mères, et encore plus celles ayant des enfants de moins de cinq ans, vivent davantage de détresse psychologique que les pères. La détresse psychologique est aussi plus élevée chez les parents moins aisés financièrement.» (p. 6) Mots-clés charge mentale (5) Chaudière-Appalaches (68) conciliation famille-travail (640) COVID-19 (112) division sexuelle du travail (21) mère (1459) télétravail (16) travail domestique (145)
https://familia.ucs.inrs.ca/notice/?ID=22357
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; charge mentale; conciliation famille-travail; covid-19; division sexuelle du travail; famille; projet charge mentale; périodes historiques; québec; régions géographiques; santé; santé des travailleuses; thématiques; travail; travail domestique

The entrenchment of the ideal worker norm during the COVID-19 pandemic: Evidence from working mothers in the United States - Zanhour, Mona; Sumpter, Dana (Gender, Work and Organization, 2022)
We study shifts in the ideal worker culture as experienced by working mothers across organizations in the United States during the COVID-19 pandemic. Experiences of 53 interviewees who attended to increased responsibilities across both work and family domains revealed an entrenchment of the ideal worker culture across nearly all organizations and professions. This manifested in three levels: as (1) a reinforced ideal worker culture in the workplace through work intensification, increased competitiveness, and surface-level support; (2) the reinforcing of organizations' ideal worker norms at home, with gendered division of space and labor; and (3) experienced internalized ideal worker norms in the expectations working mothers maintained for themselves. These findings offer insight into the lives of working mothers during the COVID-19 pandemic and the challenges which have pushed many mothers to reduce work hours or leave the workforce. Highlighting the intricate nature of the entrenchment of the ideal worker culture informs implications for theory of gendered organizations and for organizational practice. © 2022 John Wiley & Sons Ltd.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; conciliation famille-travail; culpabilité des mères; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail des mères; états-unis

Enactors or reactors? Work-life border management for women in law in Nigeria - Beauregard, T. Alexandra; Adisa, Toyin Ajibade (Community, Work and Family, 2021)
Work-family border theory casts individuals as protagonists who are enactive rather than reactive in shaping borders between work and personal life domains. To what extent is this the case in strongly patriarchal contexts that constrain women’s personal agency? This qualitative study conducted with 32 female lawyers, magistrates and justices in Nigeria shows how participants engage in new border management tactics in response to context-specific institutional and social factors. Faced with public harassment and physical assault in a country where violence against women is normalised, female legal professionals restructure family borders to extend no further than their homes and retain police attachés as border-keepers. When their families are reconfigured via nonconsensual polygamous marriages, women’s work borders are strengthened by co-wives performing domestic labour and family borders are strengthened by co-wives’ assistance with job tasks, thereby reducing participants’ work-family conflict. Rather than strategically enacting work-life borders within known situational constraints, Nigerian female legal professionals react to involuntary events that limit their agency to negotiate desired work and personal lives. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; famille; intersectionnalité; maternité; nigeria; patriarcat; polygamie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Conciliation vie familiale et vie professionnelle par les femmes travaillant dans le secteur public de la santé à Lomé : quelles stratégies d’adaptation ? - Bilampoa, Gnoumou Thiombiano; Sitsopé, Toudeka Ayawavi; David, Jean Simon (Interventions Économiques, 2021)
Cet article cerne les difficultés, les défis et les stratégies mises en œuvre par les femmes soignantes à Lomé (Togo) dans la conciliation travail-famille. Les données qualitatives ont été collectées auprès de femmes soignantes dans deux formations sanitaires publiques, de leur conjoint et de leurs collègues hommes. Les résultats montrent que les normes et les pratiques culturelles ont confiné les hommes et les femmes dans leurs rôles respectifs selon la division sexuelle du travail. Ainsi, exercer des tâches domestiques est considéré comme un devoir pour les femmes, mais une transgression des normes sociales pour les hommes. Les exigences et les conditions de la profession médicale et l’insuffisance de personnels de santé rendent difficile la conciliation travail-famille pour les femmes. Pour concilier leur vie familiale et professionnelle, les femmes soignantes mettent en œuvre plusieurs stratégies d’adaptation : recours à l’aide parentale, emploi de domestiques et de répétiteurs scolaires, acquisition d’appareils électroménagers.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; care; conciliation famille-travail; famille; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; systèmes d'oppressions; thématiques; togo; travail; travail domestique; travail du care

Paid and unpaid work during the Covid-19 pandemic: A study of the gendered division of domestic responsibilities during lockdown - Borah Hazarika, Obja; Das, Sarmistha (Journal of Gender Studies, 2021)
The Covid-19 pandemic and the strategies implemented to deal with it have had economic and societal repercussions all over the world. In India, a nationwide lockdown was initiated on 25 March 2020 which continued in a diluted form as we were conducting the interviews for the paper in July 2020. The lockdown brought activities outside the home to a standstill and people were expected to stay indoors in order to ensure social distancing and break the chain of infection. The lockdown sparked its own problems and triggered discussions on issues including economic hardship and domestic violence. The question of how domestic responsibilities are shared among adults in families has also come to the forefront of debate. As hired part-time help was discontinued under lockdown, parents who had hitherto outsourced childcare and housework were suddenly left to fend for themselves. This article attempts to explore the manner in which such unpaid domestic responsibilities, especially childcare, were shared between parents in middle-class homes. The gendered nature of this division of housework and care work, and its varied implications on the paid work and careers of mothers and fathers, is the focus of inquiry. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; 2020-2029; asie; conciliation famille-travail; confinement; covid-19; discipline; division sexuelle du travail; famille; inde; pandémie; projet charge mentale; périodes historiques; régions géographiques; science politique; science politique et droit; soins aux enfants; thématiques; travail; travail domestique

Emotion work and gender inequality in transnational family life - Chávez, Sergio; Paige, Robin; Edelblute, Heather (Journal of Family Issues, 2021)
This study examines the emotion work of non-migrant women as they seek to sustain family life across borders. We draw on in-depth interviews with 59 non-migrant women in Guanajuato, Mexico who had immigrant spouses in the USA to assess emotion work dynamics between partners. Our analysis reveals that non-migrant women do emotion work that entails imagining lives abroad and then tailoring emotional support that addresses the needs of spouses. We also discuss how the difficulties associated with prolonged separation leads women to suppress their own needs and feelings, which can lead to emotional burnout and marital conflict. Putting non-migrant women and their activities at the center of our analysis highlights the emotional costs of migration for those who remain behind and the ways in which emotion work is a highly gendered activity that reinforces inequality through communication. We highlight how women’s subordinated status in transnational Mexican families and the need to keep the remittances flowing help explain why emotion work falls largely on women. © The Author(s) 2021.
Keywords: 2000 à aujourd'hui; amériques; discipline; famille; le coût émotionnel de la migration; mexique; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; sociologie; thématiques; travail; travail émotionnel

“You’re a teacher you’re a mother, you’re a worker”: Gender inequality during COVID‐19 in Ireland - Clark, Serena; McGrane, Amy; Boyle, Neasa; Joksimovic, Natasha; Burke, Lydia; Rock, Nicole; Katriona O’ Sullivan (Gender, Work and Organization, 2021)
The novel coronavirus (COVID‐19) was declared a global pandemic in March 2020. Unlike previous highly contagious diseases that brought the threat of global instability this century such as SARS‐CoV, Zika virus (ZIKV), Swine flu (H1N1), and the Avian flu (H5N1), COVID‐19 was unable to be contained. Global restrictions were implemented to curb the spread of the virus, which included but were not limited to the closure of all educational institutions and the advice to engage in remote working. This study aims to understand the experience of working mothers who managed work and home duties during the COVID‐19 pandemic in Ireland. Thirty working mothers were interviewed in this study, and qualitative analyses were conducted to gain insight into their work and family life during the restrictions. The findings of the analysis indicate that working mothers have been negatively impacted by COVID‐19 in relation to their psychological well‐being, experiences of negative emotions, and the redefinition of family dynamics, in which working mothers have adopted additional and disproportionate care burden. These findings are consistent with the current research arguing that COVID‐19 has highlighted an increase in the gender gap in domestic labor as well as the undermining of career advancement for working mothers.
Keywords: approches et analyses; charge mentale; conciliation famille-travail; division sexuelle du travail; europe; famille; irelande; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; soins aux enfants; thématiques; travail; travail domestique

« La propriété d’une maison pavillonnaire dans l’imaginaire de la famille et les conditions économiques des familles avec enfants » dans Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales - Pugliese, Maude (Des imaginaires aux réalités conjugales et familiales: perspectives interdisciplinaires et internationales, 2021)
"La réalisation des projets de couple et familiaux constitue des préoccupations importantes des individus contemporains. Ces projets font l'objet de représentations sociales générées par diverses sources?: œuvres littéraires, philosophiques, scientifiques, populaires, mais aussi cinématographiques ou médiatiques. Ces représentations proposent des modèles et fournissent des supports à des imaginaires alimentant les scénarios personnels, créant des attentes qui se heurtent aux réalités quotidiennes, et qui entrainent souvent des désillusions et des déceptions, mais aussi des adaptations. Dans le but de mieux saisir les logiques à l'œuvre dans les attentes conjugales et familiales, cet ouvrage composé de treize chapitres rédigés par des chercheuses et chercheurs québécois, canadiens et internationaux (Brésil, Espagne, France, Suisse), issus de disciplines variées (anthropologie, démographie, psychologie, sexologie, sociologie et travail social), vise à mettre en évidence l'influence des imaginaires sur les itinéraires conjugaux et familiaux. La richesse des contributions à cet ouvrage collectif devrait aider à mieux saisir l'importance des études sur les imaginaires familiaux, autant pour la communauté scientifique que pour toute personne intéressée à mieux comprendre, et possiblement à mieux accompagner, les imaginaires, les attentes et les désillusions conjugales et familiales vécues par les individus et les couples."
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; europe; famille; inégalités; maternité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques

Undocumented mothers and work–family conflict in restrictive policy contexts - Straut-Eppsteiner, Holly (Journal of Marriage and Family, 2021)
Objectif Cette recherche examine la manière dont les mères latines sans papiers négocient le conflit travail-famille dans un contexte de politiques d’immigration restrictives. Arrière-plan Aux États-Unis, les femmes continuent de lutter contre les tensions entre travail et famille, et les femmes pauvres sont confrontées à des contraintes particulières. Les immigrées latinos se sont de plus en plus installées et ont fondé des familles aux États-Unis, et ont rejoint le marché du travail dans des emplois à bas salaires. Contrairement aux femmes nées aux États-Unis, ces femmes doivent faire face à des politiques d’immigration restrictives, ce qui suggère de nouveaux domaines de compréhension des inégalités intersectionnelles qui façonnent le conflit travail-famille. Méthode Les résultats sont basés sur des entretiens approfondis menés auprès de 45 mères immigrantes latinos en Caroline du Nord qui avaient une expérience du marché du travail rémunéré. Les sujets d'entretien comprenaient la famille, le travail et la migration tout au long de la vie des femmes. Résultats Les contextes politiques spécifiques au lieu, les conditions de travail, les attentes patriarcales et le manque d'accès aux réseaux de soins remettent en question la capacité des immigrantes latines à remplir le double rôle de mère qu'elles occupent à la fois en tant que pourvoyeuses de famille et en tant que soignantes et nourricières de leurs enfants. Conclusion Les attentes sociales liées à la maternité ajoutent une dimension de précarité au statut vulnérable des femmes en tant que travailleuses sans papiers et démontrent l’impact genré des politiques d’immigration. Conséquences Les politiques restrictives rendent de plus en plus difficile pour les femmes sans papiers d’obtenir ou de changer d’emploi sur le marché du travail à bas salaires. Les résultats soulignent l’importance de prendre en compte le statut d’immigrant dans les études sur les conflits travail-famille, en particulier à l’heure où les politiques ciblant les immigrés s’intensifient.
Keywords: amériques; approches et analyses; conciliation famille-travail; famille; femmes latino-américaines; femmes migrantes*; inégalités; patriarcat; politiques migratoires; projet charge mentale; racisme; régions géographiques; santé; santé mentale; sexisme; systèmes d'oppressions; thématiques; travail; travail reproductif; états-unis

Why so many women still take their husband’s last name - Duncan, Simon (The Conversation, 2020)
While some women may be actively involved in choosing their marital name, taking the man’s name remains the norm.
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; approches et analyses; cours; discipline; droit des femmes*; famille; histoire et politique; mariage; norvège; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc2264; sociologie; systèmes d'oppressions; thématiques

Still a superwoman? How female academics from the former Soviet Union negotiate work-family balance abroad - Antoshchuk, Irina A; Gevinner, Irina (Monitoring Obshchestvennogo Mneniya: Ekonomicheskie i Sotsial'nye Peremeny, 2020)
Since the 1930s, a peculiar 'working mother' gender contract was dominant in the Soviet Union formally empowering women. The pressing expectation of this contract and a necessity to combine motherhood, housework and employment led to the image of the near superwoman who 'has it all'. This paper examines whether highly-skilled Russian-speaking female academics continue to adhere to this cultural ideal striving for work-life balance after migration to the UK and Germany. Based on qualitative interviews with 22 female scholars, the article provides a typology of scenarios for negotiating professional and private life. It elaborates on how role-related partners contribute to achieving balance between paid employment and mothering and explores the consequences for women's well-being. Moreover, the study suggests a feminist approach to analyzing work-family balance, which valorises women's point of view, emphasizing motherhood, children and family relations as an essential personal and social value, while also documenting the increasing challenges faced in the realization of these life priorities. © 2020 Russian Public Opinion Research Center, VCIOM. All rights reserved.
Keywords: 2000 à aujourd'hui; 2010-2019; allemagne; asie; charge mentale; conciliation famille-travail; discipline; europe; ex-URSS; famille; femmes* russophones; projet charge mentale; périodes historiques; ressource en ligne; royaume-uni; russie; régions géographiques; sciences humaines; sociologie; thématiques; travail

Unions et désunions conjugales au Québec. Deuxième partie: Désunions et parentalité - Belleau, Hélène; Lavallée, Carmen (2020)
Ce rapport brosse un portrait descriptif des premiers résultats qui se dégagent du volet « extrapatrimonial » du projet de recherche intitulé : Unions et désunions conjugales au Québec : regards croisés sur les pratiques et les représentations sociales et juridiques de la vie à deux. L’enquête réalisée auprès de 3250 répondants âgés de 25 à 50 ans et vivant en couple vise à cerner les arrangements financiers et juridiques des familles qui comptent au moins un enfant. Les aspects tels que le souhait de se marier ou non, la garde des enfants, le support financier, le recours au contrat de vie commune et la question de l’héritage ont été abordés. Une attention particulière a été portée sur les familles recomposées afin de déterminer si certaines différences pouvaient être observées comparativement aux familles intactes. Nous tentons aussi de jeter un éclairage sur le phénomène de la beau-parentalité au Québec puisque le Code civil ne reconnaît toujours par de statut particulier au beau-parent. Notre enquête permet notamment de constater que le fait d’avoir un enfant semble influencer le désir de se marier, et ce, plus particulièrement pour les femmes. Elle nous montre aussi que la garde partagée est un idéal-type envisagé par la majorité des couples, mais qui se réalise moins fréquemment en réalité. De plus, dans les familles recomposées ayant la garde d’un ou de plusieurs enfants issus d’unions précédentes, les dépenses relatives aux enfants sont considérées comme relevant exclusivement du parent, même si le couple gère ses revenus et dépenses en commun. Bien que l’on puisse s’attendre à ce que les couples qui ont déjà vécu une séparation veuillent se protéger davantage dans une relation ultérieure, les résultats montrent qu’il n’en est rien. Enfin, l’enquête nous démontre que la durée de la cohabitation entre un enfant et un beau-parent influence la force du lien entre eux et qu’un bon nombre de beaux-parents croient qu’ils auraient droit à une garde partagée dans l’éventualité d’une rupture ou, à tout le moins, qu’ils garderaient contact quelques fois par année avec l’enfant de leur conjoint.e.
Publisher: Institut national de la recherche scientifique - Centre urbanisation, culture, société
Keywords: 2000 à aujourd'hui; 2010-2019; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; droits des femmes*; famille; famille recomposée; hétérosexualité; parentalité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques

L'amour conjugal sous l'angle sociologique: des pratiques à la théorie - Belleau, Hélène; Piazzesi, Chiara; Seery, Annabelle (Institut national de la recherche scientifique, 2020)
Cet article propose une réflexion sociologique sur l’amour conjugal contemporain d’un point de vue théorique et empirique. À partir de données recueillies sur les arrangements financiers de personnes vivant en couple et de la littérature sociologique sur l’amour, les auteures dégagent une sémantique de la conjugalité contemporaine illustrée par huit « règles de sens », mobilisées par les acteurs pour répondre aux défis des relations intimes. L’analyse permet d’observer les décalages entre différentes logiques amoureuses d’une part, et de l’autre entre les logiques de l’amour et les réalités sociales. Les propos des conjoints révèlent l’intégration d’éléments qui tiennent de logiques divergentes dans un même univers de sens : des règles de sens favorisant l’idéalisation mythique conjuguées à celles organisées autour des images du travail sur la relation, de la communication thérapeutique et de la prise en charge entrepreneuriale de la relation. Cette analyse empirique conduit les auteures à cerner une double confusion dans la littérature contemporaine sur l’amour et les couples.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; couple; cours; discipline; famille; hétérosexualité; inégalités; premier cycle; privilèges; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Capturing conflicting accounts of domestic labour: The household portrait as a methodology - Christopher, Emily (Sociological Research Online, 2020)
Drawing on data from a UK study conducted in 2014/2015, based on qualitative interviews with 25 working parent, heterosexual couples on their domestic division of labour, I argue that the interactive methodology of the ‘Household Portrait’ not only provides data on the distribution of household labour but also reveals gender differences in how domestic labour is conceptualised and measured. Disagreements and inconsistencies between couples over who ‘mostly’ does various tasks embody gendered perceptions of the meaning of doing domestic tasks and the appropriate temporal frame for evaluating individual contributions. Partners’ joking competition over their respective contributions highlight not just the normative expectations guiding what women and men feel they should do but also the criteria that they think should be used to measure their contributions. © The Author(s) 2020.
Keywords: approches et analyses; charge mentale; couple hétérosexuel; discipline; europe; famille; projet charge mentale; royaume-uni; régions géographiques; répartition des tâches domestiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Return of the 1950s housewife? How to stop coronavirus lockdown reinforcing sexist gender roles - Chung, Heejung (2020)
Alors que le virus COVID-19 se propage à travers le monde, de nombreux gouvernements ont fermé les écoles , les crèches et autres établissements de garde d'enfants. Avec de plus en plus de personnes travaillant à domicile , il est probable que de nombreuses familles se retrouveront dans une situation où les deux parents essaient de travailler depuis la table de la cuisine tout en essayant de faire l'école à la maison aux enfants . En plus des tâches ménagères habituelles, comme la cuisine et le ménage, ces tâches peuvent représenter une charge supplémentaire pour de nombreux parents à l'heure actuelle. Il est cependant probable que même si les deux parents sont désormais à la maison, une grande partie des tâches « domestiques » reposera toujours sur les épaules des femmes de la maison. Tout comme la ménagère des années 1950, les femmes devront non seulement préparer des repas savoureux, garder la maison propre et bien rangée et divertir les enfants, mais elles devront également faire tout cela tout en travaillant à domicile.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; charge mentale; conciliation famille-travail; covid-19; discipline; famille; pandémie; projet charge mentale; périodes historiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique

Représentations et récits pluriels au sein des familles homoparentales: Reconnaître la diversité familiale pour mieux contrer l’hétéronormativité - Côté, Isabel; Lavoie, Kévin (Service social, 2020)
Cet article propose une mise en récit du parcours de deux chercheur·e·s dont les intérêts de recherche et d’enseignement portent sur les familles issues de la diversité sexuelle. En mettant à l’épreuve le modèle hétéronormatif traditionnel, les familles homoparentales, notamment celles qui ont recours à la procréation assistée, font émerger de nouvelles trames familiales et relationnelles, en plus de rendre visibles les normes culturelles associées à la parenté, à la parentalité et à la concrétisation du désir d’enfant. Dès lors, une compréhension de la diversité familiale en adéquation avec les pratiques sociales contemporaines s’actualise par une prise en compte de la pluralité des expériences vécues par les parents de même sexe et de leurs enfants.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; famille; homoparentalité; hétéronormativité; inégalités; maternité; parentalité; patriarcat; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; sociologie; systèmes d'oppressions; thématiques

Le « parent hélicoptère » et le paradoxe de la parentalité intensive au XXIe siècle - Ellie Lee; Jan Macvarish (Lien Social et Politiques, 2020)
Le terme « parent hélicoptère » est aujourd’hui très présent dans les discours public et professionnel sur l’éducation des enfants, ainsi que dans la culture de façon plus générale, particulièrement en Amérique du Nord et au Royaume-Uni. Un petit nombre de travaux sociologiques ont mis en évidence le caractère paradoxal de ce phénomène, qui réside dans une inquiétude souvent exagérée envers l’investissement « excessif » de ces parents dits « hélicoptères » auprès de leurs enfants, au sein même d’une culture de la parentalité intensive. Cet article développe ces travaux de deux manières. Nous resituons d’abord l’utilisation désormais omniprésente du terme « parent hélicoptère » et les qualificatifs qui y sont associés en examinant ses antécédents discursifs dans la terminologie du XXe siècle — comme l’overparenting (surparentalité), le smothering (parent poule ou parent qui couve) ou le coddling (dorlotement) — et en soulignant leur coexistence avec les récits de « mauvaises mères », considérées comme distantes et non impliquées. Ensuite, en analysant l’utilisation du terme helicopter parent faite dans les médias britanniques depuis la fin du XXe siècle, nous analysons comment se construisent les préoccupations actuelles concernant le surinvestissement des parents dans l’éducation de leurs enfants. Nous avons observé que les thèmes les plus récurrents de la couverture médiatique concernaient l’amour parental qui a mal tourné (gone wrong), la pression parentale (parental pushiness), ainsi que la classe sociale du parent hélicoptère. Notre analyse suggère que l’expression « parent hélicoptère » peut être mieux comprise comme un aspect du langage vernaculaire du XXIe siècle qui exprime une certaine aversion envers les résultats perçus d’une parentalité intensive, mais qui laisse intactes les prémisses concernant la responsabilité parentale en matière de pathologies individuelles et sociales. Nous concluons que, pour les sociologues, une caractéristique importante du parent hélicoptère est qu’il est généralement perçu comme un parent « à problèmes » issu de la classe moyenne, et nous suggérons que cette construction de l’origine sociale des défaillances parentales est une question importante à prendre en considération à l’avenir dans les études sur la culture de la parentalité.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; famille; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; états-unis

The care ceiling in higher education - Lynch, Kathleen; Ivancheva, Mariya; O'Flynn, Micheál; Keating, Kathryn; O'Connor, Monica (Irish Educational Studies, 2020)
This study examines the impact of managerialist policies on care relations in higher education. It is based on a study of 10 higher education institutions in Ireland. The paper shows that a care-free worker model is ingrained in systems of performance appraisal, especially for academics in universities, and increasingly in the Institutes of Technology, although it also impacts on support staff in other professions and occupations. It assumes a life of boundary-less working hours and unhindered mobility. The market-informed tools of performance appraisal, especially audits and metrics, cannot measure essential care work because care is a process and disposition, not a product. Because it is not countable caring becomes invisible as do the people who do it. The managerial ideology of 'work–life balance' merely operates as a mask that conceals how over-working is normalised. There is no legitimate language to name over-working for the structural problem that it is. When work organisations disregard care commitments outside of work, and even within it, these are then repackaged and fed back to women/carers as personal problems and failures. The idealised care-free worker model operates as a care ceiling over women particularly; it is taken as given, even natural.
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; conciliation famille-travail; europe; famille; femmes universitaires*; irlande; patriarcat; politiques néolibérales; projet charge mentale; périodes historiques; rapports sociaux de sexe; rentabilité; régions géographiques; systèmes d'oppressions; thématiques; travail; travail du care

Évolution et transformation de la politique familiale québécoise depuis 1997 - Mathieu, Sophie; Tremblay, Diane-Gabrielle (Enfances, Familles, Générations, 2020)
Cadre de la recherche : Le consensus établi autour de l’exceptionnalisme de la politique familiale québécoise dissimule certains enjeux et défis liés à l’accessibilité et à la disponibilité des mesures de soutien aux familles. Objectifs : L’objectif de la recherche consiste à proposer une réflexion sur le caractère universel souvent attribué à la politique familiale québécoise en documentant l’évolution de l’architecture des trois principales mesures de soutien aux familles depuis 1997, soit les services de garde, les congés parentaux et les prestations monétaires. Méthodologie : Le texte repose sur une revue systématique d’archives, de documents gouvernementaux et de recherches scientifiques sur l’évolution et la transformation de la politique familiale québécoise. Le point de départ de l’analyse est l’examen du Livre blanc Nouvelles dispositions de la politique familiale : les enfants au cœur de nos choix. Résultats : En dépit de son penchant social-démocrate, la politique familiale québécoise n’est pas universelle dans son ensemble et toutes les familles ne sont pas égales dans le soutien qu’elles reçoivent de l’État. Nous montrons l’existence historique de quatre régimes de service de garde, dont les caractéristiques varient selon la nature des services offerts, leurs coûts et la possibilité d’y avoir accès. Nous montrons aussi qu’en raison de l’architecture du Régime québécois d’assurance parentale (RQAP), certains parents ne se qualifient pas pour l’obtention de prestations parentales. Enfin, nous montrons que même si toutes les familles reçoivent depuis 2005 des prestations monétaires, le montant de ces dernières varie selon le revenu. Conclusions : Même si le Québec offre une politique familiale généreuse, la province n’échappe pas entièrement aux caractéristiques des sociétés libérales, dont le Canada fait partie. Contribution : L’article contribue à la réflexion sur la perspective universaliste attribuée à la politique familiale québécoise.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; famille; histoire et politique; inégalités; justice sociale; maternité; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

The missing doctors — An analysis of educated women and female domesticity in Pakistan - Mohsin, Mariam; Syed, Jawad (Gender, Work and Organization, 2020)
While the percentage of female students in medical schools in Pakistan is as high as 80–85 per cent, the percentage of female doctors in the medical workforce remains below 50 per cent. Our findings draw on in-depth interviews with 31 female doctors to show that the reasons behind the gap between female medical students and female medical professionals are multifold and multilayered, ranging from individual reasons to organizational and sociocultural reasons. We use an adapted version of the relational framework developed by Syed and Özbilgin in 2009 to offer a contextual and multilevel understanding of female domesticity in Pakistan. The study suggests that the problem of female doctors dropping out of the medical workforce is a reflection of the interplay of social, organizational and individual factors, which are tied together by social norms. Practical implications suggest that making hospitals and health organizations more inclusive of women and their needs could be a starting point for policymakers to address the gender gap in the medical profession. © 2020 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2010-2019; asie; conciliation famille-travail; famille; femmes* médecins; maternité; pakistan; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail

The COVID-19 pandemic has increased the care burden of women and families - Power, Kate (Sustainability: Science, Practice and Policy, 2020)
While women were already doing most of the world’s unpaid care work prior to the onset of the COVID-19 pandemic, emerging research suggests that the crisis and its subsequent shutdown response have resulted in a dramatic increase in this burden. It is likely that the negative impacts for women and families will last for years without proactive interventions. What we commonly refer to as “the economy” would not function without the (often unrecognized) foundation of work provided by the “care economy”: the reproduction of everyday life through cooking, raising children, and so forth. The paid economy has slowed not only because people are physically not allowed into workplaces, but also because many families currently need to raise and educate their children without institutional support, which is reducing remunerated working hours and increasing stress. It has long been recognized that gross domestic product ignores the care economy and heterodox economists have promoted alternative economic systems that could value care work and facilitate a fairer sharing of domestic labor while promoting environmental and economic sustainability. This policy brief builds on recent work on the care economy to explore implications of the COVID-19 pandemic and opportunities for addressing the burden of unpaid care work.
https://cieg.unam.mx/covid-genero/pdf/reflexiones/academia/the-care-burden.pdf
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; care; covid-19; famille; genre; périodes historiques; ressource en ligne; thématiques; travail

Labor market outcomes of professional women with two children after the one‐child policy in China - Shen, Yang; Lai, Jiang (The Journal of Social Issues, 2020)
Since the implementation of the two‐child policy in China in 2016, it is unclear how professional women's labor force outcomes and family commitments have changed. Using interviews with 26 professional women with two children in Shanghai, we examined their work–life transitions and labor market outcomes. We found that the overarching constraints the interviewees faced included a lack of institutional childcare support, low paternal participation and increased physical and cognitive childcare labor. The women also experienced different constraining and enabling factors, leading to four types of labor market outcomes: enhancement, rebound, interruption and stagnation. Most of the interviewees who experienced career upward mobility after giving birth to a second child were urban singleton daughters who received tremendous parental support. Some participants experienced career interruption due to a lack of social support. The state should ensure family‐friendly work environments and promote paternal participation to reduce women's work–life conflict and address gender inequality.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; chine; conciliation famille-travail; famille; inégalités hommes-femmes; maternité; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; sexisme; soutien familial; systèmes d'oppressions; thématiques; travail; travail reproductif; travail rémunéré

Concilier famille et travail dans un horaire atypique ? - Souissi, Takwa (Gazette des femmes, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; thématiques; travail; travail de la construction; travail domestique

Work-family balance and the subjective well-being of rural women in Sichuan, China - Yue Shui; Xu, Dingde; Liu, Yi; Liu, Shaoquan (BMC Women's Health, 2020)
Background Due to the great burden of family and the conflicts among family, society and career roles resulting from migrant working, rural women suffer more conflicts between work and family and need more social attention. Previous studies of the conflicts between family and work mainly focus on the group of career women, and there is a lack of the research on the conflicts between work and family of rural women, which needs to be systematically and further studied.Methods This study used a sample survey of 380 rural women in rural areas of Sichuan Province to measure rural women’s cognition of work-family, coordination and handling of conflicts, post-conflict choices, and subjective well-being; the study constructs an ordered multi-class logistic regression model to explore the impact of work-family conflict on the subjective well-being of rural women in rural regions.Results The study result shows that: (1) The level of subjective well-being of rural women is generally high, and 70% of women feel satisfied or very satisfied. (2) The factor which impacts the subjective well-being among rural women most is work-interfering-with-family conflict, followed by work-family balance and confidence in conflict coordination.Conclusion This study can enhance our understanding of rural women in rural areas, and provide a reference for formulating policies to improve people’s life satisfaction.
Keywords: 2000 à aujourd'hui; 2010-2019; asie; bien-être psychosocial; chine; conciliation famille-travail; famille; femmes rurales; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail